1998
DOI: 10.1117/12.328092
|View full text |Cite
|
Sign up to set email alerts
|

ISIS: an information-efficient spectral imaging system

Abstract: A specialized hyperspectral imager has been developed that preprocesses the spectra from an image before the light reaches the detectors. This "optical computer" does not allow the flexibility of digital post-processing. However, the processing is done in real time and the system can examine = 2 x lo6 scene pixels/sec. Therefore, outdoors it could search for pollutants, vegetation types, minerals, or man-made objects. On a highspeed production line it could identify defects in sheet products like plastic wrap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In contrast, several previous studies have shown that chemometric techniques could be incorporated directly into the optical measurement process by using either static optical interference filters, 7 or tunable liquid crystal [8][9][10] or micromirror [11][12][13][14][15] based multivariate optical elements built into the spectrometer hardware. The general principle of these filters is to combine photons of various frequencies in a prescribed way in order to facilitate the estimation of a quantity of interest.…”
Section: -6mentioning
confidence: 99%
“…In contrast, several previous studies have shown that chemometric techniques could be incorporated directly into the optical measurement process by using either static optical interference filters, 7 or tunable liquid crystal [8][9][10] or micromirror [11][12][13][14][15] based multivariate optical elements built into the spectrometer hardware. The general principle of these filters is to combine photons of various frequencies in a prescribed way in order to facilitate the estimation of a quantity of interest.…”
Section: -6mentioning
confidence: 99%
“…The DMD is located on a separate, small carrier board, and is connected to the controller via ribbon cables. 15 HostPC 3. SPECTROMETER DESIGN Using the new controller, a simple transmission grating spectrometer was constructed to demonstrate the DMD-MOS technology.…”
Section: Fifomentioning
confidence: 99%
“…This paper describes aircraft flight campaign test results for the Imaging spectral signature instrument (ISSI) breadboard developed in the ESA contract 19754/06/NL/PA. The ISSI project was inspired by the Informationefficient hyperspectral imaging sensor (ISIS) [1]. The development and design of the ISSI breadboard is described in [2].…”
Section: Introductionmentioning
confidence: 99%